Medicinal Plant Used Against Cancer: A Review - Srivastava, Rajat; Tiwari, Priya (Asian Journal of Pharmaceutical Research and Development, 2022)
Nowadays natural products are considered protective markers compared to synthetic products that are considered unsafe for human health and the environment. Although a large number of synthetic drugs have been added to the world of current pharmacopoeia, there is still no drug system in the world that has been able to solve all health problems, including diseases such as Cancer. The extracts from plants have played an important role in the development of clinically effective anti-cancer agents. The plant kingdom produces naturally occurring secondary metabolites that are being investigated for their anti-cancer activities leading to the development of new clinical drugs. Global results continue to identify new anticancer compounds from plants. In recent years out of fear of adverse effects, people have chosen to make greater use of natural cancer products. This review attempted to summarize a few plants in India and outside India that have anti-cancer activity.